2017
DOI: 10.5103/kjsb.2017.27.2.149
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Stability on Single-leg Standing by Wearing a Head Mounted Display

Abstract: Objective: The purpose of this study was to investigate the effects of three visual conditions (eyes opened, eyes closed, and wearing of a head mounted display [HMD]) on single-leg standing through kinematics and kinetic analysis.Method: Twelve college students (age: 24.5±2.6 years, height: 175.0±6.4 cm, weight: 69.2±5.1 kg) participated in this study. The study method adopted three-dimensional analysis with six cameras and ground reaction force measurement with one force plate. The analysis variables were coe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…showed that the COP area and oscillations increase in single-leg balance 14 . The device did not assess balance in displacements of the head or upper limbs.…”
Section: Introductionmentioning
confidence: 98%
“…showed that the COP area and oscillations increase in single-leg balance 14 . The device did not assess balance in displacements of the head or upper limbs.…”
Section: Introductionmentioning
confidence: 98%